Type I Interferon and the Spectrum of Susceptibility to Viral Infection and Autoimmune Disease: A Shared Genomic Signature - Sugrue, Jamie A.; Bourke, Nollaig M.; O’Farrelly, Cliona (Frontiers in Immunology, 2021)
Type I interferons (IFN-I) and their cognate receptor, the IFNAR1/2 heterodimer, are critical components of the innate immune system in humans. They have been widely explored in the context of viral infection and autoimmune disease where they play key roles in protection against infection or shaping disease pathogenesis. A false dichotomy has emerged in the study of IFN-I where interferons are thought of as either beneficial or pathogenic. This ‘good or bad’ viewpoint excludes more nuanced interpretations of IFN-I biology - for example, it is known that IFN-I is associated with the development of systemic lupus erythematosus, yet is also protective in the context of infectious diseases and contributes to resistance to viral infection. Studies have suggested that a shared transcriptomic signature underpins both potential resistance to viral infection and autoimmune disease. This seems to be particularly evident in females, who exhibit increased viral resistance and increased susceptibility to autoimmune disease. The molecular mechanisms behind such a signature and the role of sex in its determination have yet to be precisely defined. From a genomic perspective, several single nucleotide polymorphisms (SNPs) in the IFN-I system have been associated with both infectious and autoimmune disease. While overlap between infection and autoimmunity has been described in the incidence of these SNPs, it has been overlooked in work and discussion to date. Here, we discuss the possible contributions of IFN-Is to the pathogenesis of infectious and inflammatory human diseases. We comment on genetic associations between common SNPs in IFN-I or their signalling molecules that point towards roles in protection against viral infection and susceptibility to autoimmunity and propose that a shared transcriptomic and genomic immunological signature may underlie resistance to viral infection and autoimmunity in humans. We believe that defining shared transcriptomic and genomic immunological signatures underlying resistance to viral infection and autoimmunity in humans will reveal new therapeutic targets and improved vaccine strategies, particularly in females.